Pendidikan Karakter dalam Tepukan Tiga Kali pada Pembelajaran Bahasa Indonesia di SMP - Harum Suparmini; Mukti Widayati; Nurnaningsih Nurnaningsih (Lembaga Sosial Rumah Indonesia, 2023)
Character education is now necessary for the survival of a nation in the midst of rapid and dramatic social change. This study aims to reveal and describe character education in a collection of short stories by Wicahyanti Rejeki and its relevance in learning Indonesian in junior high school. This research belongs to the category of literary research with a qualitative descriptive form, using a literary sociology approach with the content analysis method. The data used in this research is a collection of short stories Tepukan Tiga Kali by Wicahyanti Rejeki. The data analysis techniques used are dialectical techniques and interactive techniques. The results showed that the first five short stories from the Tepukan Tiga Kali short story collection studied contained character education values. Character education contained in the five short stories include: faith and piety in God Almighty, global diversity, mutual cooperation, independence, critical reasoning, and creativity. Secondly, the character education values contained in the collection of short stories can help achieve the educational objectives of Indonesian language lessons. The implications of moral and character values contained in literary works play a role in developing cognitive, affective, psychomotor aspects, developing personality, and developing the social personality of junior high school students.